Age-Related Deficits in Reality Monitoring of Action Memories - McDaniel, Mark A. (2008)
We describe three theoretical accounts of age-related increases in falsely remembering that imagined actions were performed (Thomas & Bulevich, 2006). To investigate these accounts and further explore age-related changes in reality monitoring of action memories, we used a new paradigm in which actions were (a) imagined-only (b) actually performed, or (c) both imagined and performed. Older adults were more likely than younger adults to misremember the source of imagined-only actions, with older adults’ more often specifying that the action was imagined and also that it was performed. For both age groups, as repetitions of the imagined-only events increased, illusions that the actions were only performed decreased. These patterns suggest that both older and younger adults utilize qualitative characteristics when making reality-monitoring judgments and that repeated imagination produces richer records of both sensory details and cognitive operations. However, sensory information derived from imagination appears to be more similar to that derived from performance for older than younger adults.